Analisis Teknikal Sebagai Dasar Pengambilan Keputusan dalam Trading Saham pada Bursa Efek Indonesia (Studi pada BBCA dan BBRI Januari-Juni 2024) - Masnawaty Sangkala (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to examine stock price movements using the Bollinger Bands (BB) and Relative Strength Index (RSI) indicators as a reference in making stock buying and selling decisions. The data analyzed includes daily movements of PT Bank Central Asia Tbk (BBCA) and PT Bank Rakyat Indonesia Persero Tbk (BBRI) shares during the period January-June 2024. The research method utilizes the BB indicator to measure volatility and price movement patterns, as well as RSI to detect overbought and oversold conditions. The results show that optimal stock purchases occur when the price is outside the BB lower band line with an RSI value below 30. Conversely, optimal stock sales are made when the price is outside the BB upper band line with an RSI value above 70. The combination of these two indicators proves effective in producing more accurate transaction signals, thus helping investors determine the timing of transactions more precisely. This research provides practical benefits for investors in applying technical analysis to reduce the risk of loss and increase profit opportunities in the capital market.